2016
DOI: 10.5812/ijp.3834
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Preschool Teachers Regarding Attention Deficit Hyperactivity Disorder

Abstract: Background: The symptoms of attention deficit/hyperactivity disorder (ADHD) may manifest before the child begins elementary school. Objectives: To survey preschool teachers' knowledge and attitudes regarding ADHD. Methods: In this cross-sectional study, 360 preschool teachers were selected via a randomized cluster sampling method from among the teachers working in Tabriz, Iran, during 2013. A self-administered questionnaire concerning the symptoms of ADHD, the method of diagnosis, and their attitudes regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…(13) These result in same line with our finding. The finding of Amiri, Noorazar, Fakhari, Darounkolaee, & Gharehgoz, (2017) consistent with current finding (14) . They found that majority of teachers were females.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…(13) These result in same line with our finding. The finding of Amiri, Noorazar, Fakhari, Darounkolaee, & Gharehgoz, (2017) consistent with current finding (14) . They found that majority of teachers were females.…”
Section: Discussionsupporting
confidence: 86%
“…Amiri, Noorazar, Fakhari, Darounkolaee, & Gharehgoz, (2017) found that almost half of the teachers believed that the educational system plays a very important role in perpetuating the symptoms of ADHD, while nearly half believed that special schools are needed. Although almost one third of teachers believed that the behavior of children with ADHD is deliberate in nature, fewer believed that punishment is needed and even fewer blamed the children's family for their behavior (14) . This finding is consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Developing by researchers, a self-reported questionnaire was used to data collection. This questionnaire was developed based on a review of the literature to assess teachers' knowledge, attitudes, and behaviors to support children with ADHD (8,12,14,15,18,19). An expert's panel who were selected based on their quali cations and experience in health education, psychology, and ADHD determined the face validity and content validity of the questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…When children with ADHD present in class with their peers and friends, their teachers face numerous challenges (4,18,19). Therefore, elementary school teachers need e cient knowledge about problems and special needs of the children with ADHD and they have to plan effective behavior management strategies in dealing with those children (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation